Influence of Lactobacillus brevis on metabolite changes in bacteria‐fermented sufu. Issue 1 (3rd January 2020) - Bao, Wenjing; Huang, Xiaoning; Liu, Jingjing; Han, Beizhong; Chen, Jingyu
Abstract: Sufu is a form of food derived from traditional Chinese fermented soybean. It has a unique flavor and contains abundant nutrients. With demands for healthy food on the rise, a higher level of sufu functionality is required. In fermentation of soybean‐derived products, lactic acid bacteria (LAB) are widely used as an adjunct culture, which provides health benefits and enhances flavor of food. Among LAB, Lactobacillus brevis has the potential to generate γ‐aminobutyric acid (GABA), which is well‐known for its physiological functions. In this study, L. brevis was added to bacteria‐fermented sufu to evaluate its impacts on sufu quality. Sufu was produced via co‐inoculation with Bacillus subtilis and L. brevis (group A sufu) or a single inoculation with B. subtilis (group B sufu). Metabolite changes in the two groups during fermentation were investigated and physicochemical changes were observed. The results indicated that the addition of L. brevis increased the concentration of GABA and decreased the concentrations of histamine and serotonin. The concentrations of volatile compounds, such as esters and acids, especially 2‐methyl‐butanoic acid ethyl ester, as well as the concentrations of phenylethyl alcohol and 3‐methyl‐butanol were significantly higher in group A. Inoculation of L. brevis changed the metabolite profile of sufu and improved its functionality and safety of edibility. The current study explored the potential of applying L. brevis to the manufacture of bacteria‐fermented sufu.